PENGARUH KOMPOSISI NANO SEMEN TERHADAP KUAT TEKAN MORTAR - Dion Aji Fadlillah; Frisky Sustiawan; Han Ay Lie; Purwanto Purwanto (Jurnal Karya Teknik Sipil, 2014)
The micro voids in the cement paste of cementitious material drastically reduce the load-carrying capacity of the element, due to the reduction in area. On the other hand, the weak interface between aggregates and mortar induces micro-crack initiation and promote crack propagation. It therefore becomes curial to reduce the voids in the mortar, and promotes a better hydration degree of cement. A method that has been proven effective is the use of nano-cement particles. The smaller cement particles will result in a better hydration process, and create less large ettringites and calcium hydrates. This research work studied the effect of nano-cement percentage in the mortar mix by the substitution method. The ratio in weight of the nano-cement with respect to the normal cement ranged from 0%, 20%, 40%, 60%, 80%, to 100%. The specimens sized 50 × 50 × 50 mm were tested at the age of 28 days to obtain their compression strength. The cement-to-sand proportion was 1 to 2.75, while a water-cement-ratio of 0.485 was maintained throughout the experiments. Two cement types, PCC (Portland Composite Cement) and PPC (Portland Pozzolane Cement), all Indonesian based products, were compared to obtain a picture of the overall cement condition in Indonesia, and the effectiveness of the nano-cement use to each of the types.